Theoretical and innovative concept of technological processes in heat and power system constructions - Zhuravska, N. (Ways to Improve Construction Efficiency, 2018)
The article discusses the thermodynamic concept of innovative processes, the thermodynamic concept of non-reagent preparation of industrial water of thermal power plants. Thermodynamic functional characteristic is presented in heat and power construction systems with non-reagent water purification in electromagnetic fields. It is noted, as regards biological impurities in water, that this method eliminates the accumulation of salts in the pipeline, biological damage, as the occurrence of potentially possible critical man-made situations.